Halal vs non-halal cosmetic: Positioning in Malaysian market / Azahar Harun … [et al.] - Harun, Azahar; Naseri, Roszi Naszariah Nasni; Zolkifly, Nur Hazwani (2017)
An increase of global Muslim population contributes to booming in Halal market. Halal Industries Development Organization predicted that the population will rise to over 30% of the world population by 2030 thus contributes to changing landscape of cosmetic buying behavior among Muslim consumer. Unfortunately, Halal cosmetic products suffer from poor product positioning strategy which makes it difficult to compete with non Halal brands. Therefore, this conceptual paper aims to explore the dimensions that consumers use to evaluate products offered in the market thus proposing a conceptual framework namely Halal Cosmetic Positioning Model (HCPM). Through document reviews, four dimensions i.e. Halal label, product quality, product ingredients and safety have been identified to differentiate Halal cosmetics with non Halal brands. The findings shall be find useful for manufacturers, producers, and marketers of Halal cosmetics in strategizing effective positioning strategies thus capturing Malaysian markets. The outcomes of the study can be verified further by using empirical methods to validate each dimension.